Quantitative analysis of usability issues of E-commerce portals. Issue 4 (4th July 2017) - Gautam, Anju; Saxena, Prashant Sahai; Shiwani, Savita
Abstract: Internet plays a vital role in various domains such as academics, multimedia banking, exchange of data and information. The trend of online shopping is increasing by leaps and bounds. With the growing demand of Internet requires continuous evaluation of user interface of the online shopping portals. There are number of usability problems exist in B2Commerce portals. This paper measures the different usability issues of E-Commerce shopping portals as per user perspective. The present study works on End user testing method.